The Effectiveness of the Technopark Program in Efforts to Prepare Start-Up Business - Hariani Aprillia; Widiyanti; Didik Nurhadi (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
One of the government's commitments to improve the quality of the workforce in Indonesia is to develop vocational education and training through the technopark program. The purpose of the study was to determine the effectiveness of the technopark program at SMK Negeri 3 Malang.The research method uses a qualitative approach with indicators: efford, cost efficiency, result and impact. Data analysis using the Miles and Huberman model includes: reduction, display and verification. The results of this study revealed that the implementation of the technopark program at SMK Negeri 3 Malang was quite successful in increasing the number of entrepreneurs.